Uruguay Round and Third World sovereignty - Khor Kok Peng, Martin (Third World Network PenangMY, 1990)
Explains the North-South conflict in approaching the central issues that lie at the core of the Uruguay Round. Portrays the Uruguay Round as a battleground between the advocates of a more fair and ecological world and those desiring a world order ruled by transnational companies.